Decentralized optimization for coordinated participation of local energy communities in ancillary services markets with desired energy sharing and costs - Pierluigi Siano; Marialaura Di Somma; Mohammad Dolatabadi (International Journal of Electrical Power & Energy Systems)
Achieving the multiple benefits associated with Local Energy Communities (LECs) for both community members and grid operators requires advanced energy management through inter-community coordination, optimizing virtual energy sharing and ancillary service (AS) provision. This task is challenging because local requirements must be considered alongside global ones; individually, each LEC might be unable to guarantee sufficient power flexibility, which becomes feasible through coordinated efforts among multiple communities. This paper presents a novel inter-community coordination method, based on decentralized optimization to ensure the joint participation of multiple LECs in the AS market. The proposed coordination method considers as objective function the remuneration for AS provision combined with revenues associated with the incentives for the energy shared as established by the Italian regulation, while energy costs are considered as a constraint. In addition, the proposed method allows the LEC manager to assess the impact of peer-to-peer (P2P) energy exchanges on the coordination of LECs, the incentives for virtual energy sharing and the remuneration for AS provision. Multiple case studies are analyzed to evaluate the performance of the proposed method for two LECs, and the results demonstrate its effectiveness for inter-communities’ coordination while keeping the energy shared close to the desired value and the energy costs unchanged. P2P energy exchanges in each LEC tend to reduce energy costs and increase the self-consumption rate, while their impact on the provided flexibility depends on PV energy production. Under a coordinated management obtained with the proposed decentralized optimization, each LEC’s objective function remains within roughly 1 % of its ideal solution. In summer scenarios, joint flexibility increases each community’s economic objective from approximately €659–€745 to €2154 and €1601, respectively, highlighting that revenue from ancillary services can easily compensate for any reductions in shared-energy incentives. In winter scenarios, with lower PV energy production, flexibility revenues decrease, yet the communities remain within 1% of their optimal local targets, further demonstrating the method's effectiveness.